Molecular mechanisms of ferroptosis and its role in cancer therapy. Issue 8 (24th June 2019) - Xu, Tao; Ding, Wei; Ji, Xiaoyu; Ao, Xiang; Liu, Ying; Yu, Wanpeng; Wang, Jianxun
Abstract: Ferroptosis is a newly defined programmed cell death process with the hallmark of the accumulation of iron‐dependent lipid peroxides. The term was first coined in 2012 by the Stockwell Lab, who described a unique type of cell death induced by the small molecules erastin or RSL3. Ferroptosis is distinct from other already established programmed cell death and has unique morphological and bioenergetic features. The physiological role of ferroptosis during development has not been well characterized. However, ferroptosis shows great potentials during the cancer therapy. Great progress has been made in exploring the mechanisms of ferroptosis. In this review, we focus on the molecular mechanisms of ferroptosis, the small molecules functioning in ferroptosis initiation and ferroptosis sensitivity in different cancers. We are also concerned with the new arising questions in this particular research area that remains unanswered.